Ukuran Omfalokel: Apakah Berhubungan dengan Anomali Kongenital ? - Prajitno Sugianto (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2020)
ABSTRACT                                                                     Background: Omphalocele (also known as exomphalus) is a condition that is seen in newborn infants, and is thought to result from failure of the intestines to return to the abdomen after the migration into the umbilical cord. Omphalocele is often associated with the presence of other congenital anomalies. One study says that a small of defect omphalocele is often accompanied by intestinal disorders and have a better prognosis. Purpose(s): Based on this study the researcher wants to review the relationship between the size of  omphalocele defect and the presence of associated congenital anomaly in Hasan Sadikin Hospital. Methods: This is a retrospective cross-sectional study. All patient with omphalocele between February 2007 – March 2012 were included in this study. Data collected were patient demographics, size of omphalocele defect and congenital anomalies identified. In this study, patients were  designated as those with large (greater than 4 cm) or small (4 cm and less) defect omphaloceles. This study analyzed correlation between size of defect with associated anomaly using Fisher exact test  and  p < 0.05 is considered to be significant. Results: There were 52 omphalocele cases (24 girls, 28 boys), median birth weight 2710gr (range 1300gr–4000gr). Twenty seven patients were classified as small defect, with 25 classified as large defect. Anomaly found in the small defect groups consists of facial anomaly (7%); cardiac anomaly (7%); intestinal disorder (22%,P=0,02) include patent omphalomesentericus duct, anorectal malformation and cloaca extrophi; limb anomaly (7%). Meanwhile, anomalies identified in the large defect group consist of facial anomaly (8%); cardac defect (32%) include dextrocardi and tetralogi Fallot; limb anomaly (16%).In this study, cardiac defects was significantly higher in the large defect group, meanwhile intestinal diorder is statistically significant in small defect groups. Conclusion: Small defect omphalocele correlates with an increased prevalence of associated gastrointestinal anomalies and a lower prevalence of cardiac anomalies.Keyword: Omphalocele; Exomphalus; Associated congenital anomalies; Defect size